Robotics-Assisted Pediatric Oncology Surgery—A Preliminary Single-Center Report and a Systematic Review of Published Studies - Vatta, Fabrizio; Gazzaneo, Marta; Bertozzi, Mirko; Raffaele, Alessandro; Avolio, Luigi; Riccipetitoni, Giovanna (Frontiers in Pediatrics, 2022)
Aim: The use of robotic-assisted surgery in oncology has been proved effective and safe in adults. Despite these results, use of robotics has been rarely reported in pediatric oncology. Our review aims to evaluate the safety and feasibility of robotic surgery in this field, comparing our experience to the most recent literature. Methods: Review of all patients affected by an oncological disease who underwent a robotic-assisted procedure at our Institute. Systematic review of the literature from 2012 to 2021 on the subject. Findings: A total of 14 patients underwent robotic-assisted tumor resection. 11 procedures(median age 13.2 years-old) were carried out in children with annexal lesions(seven tumor excision and four ovariectomy). Histological diagnosis was mature teratoma (six), serous papillary cystadenofibromas of the fallopian tube(two), ovarian serous cystoadenoma(one), ovarian mucinous cystoadenoma(one), and ovarian sero-mucinous cystoadenoma. Median length of stay was 2 days. No recurrences or complications at a median follow-up of 2.1 years were observed. A 5-years-old girl underwent a complete posterior resection of a type-3 sacro-coccygeal tumor with a robotic-assisted approach for the dissection of a possible intraabdominal residual component of the lesion. No intra- and post-operative complications were recorded. A complete excision of a recurrent differentiating neuroblastoma of the left para-renal region was performed on a 9-year-old girl. An idiopathic anaphylactic shock occurred one day after the procedure. At 9 months follow-up no local recurrences of the lesion were observed. Lastly, a robotic-excision of a growing left superior mediastinal intermixed ganglioneuroblastoma was performed on an 8-years-old girl with no post-operative complications. Follow-up was uneventful(7 months). Overall we reported no conversion to open surgery. In literature rate of complications ranges from 0 to 28%.Conversion is reported in 5% of all oncological procedures, mainly due to adhesions and difficulties to evaluate correct anatomy. Conclusion: Robotic surgery in pediatric oncology has proven to be feasible. Nevertheless, its use should be limited to selected cases and performed by highly trained oncological surgeons. Preparation and patient positioning, alongside with a correct port placement, are crucial to carry out these procedures. Further innovations in robotics may allow a wider application of this technology in pediatric oncology.